2006
DOI: 10.1258/095646206776253435
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal colonization with Candida spp. in human immunodeficiency virus – infected women: a cohort study

Abstract: We have conducted a longitudinal study on factors associated with candidal vaginal colonization, a precursor of vaginitis, in a cohort of HIV-infected women in Italy. All consecutive women attending a single, tertiary care clinical site were offered free screening for sexually transmitted infections and genital disorders every 6-12 months. Candidal vaginal colonization was defined as a positive culture for Candida spp. in an asymptomatic woman. From January 1998 to July 2002 we analysed 214 women. The baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
4
19
2
Order By: Relevance
“…In other countries such as Italy and the United States, the frequency was higher ranging from 81% to 92%, compared to that found in our study (52.9%). 10,11,18 In HIV-uninfected patients, our data was similar to other studies performed in Brazil, which describe the prevalence of C. albicans isolated in vaginal samples ranging from 60% to 80% 19,20 and in other countries where the prevalence of C. albicans in vaginal samples ranges between 80% to 90%. 1,11,21,22 A higher diversity of non-albicans species was found in HIV-infected patients compared to uninfected controls.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In other countries such as Italy and the United States, the frequency was higher ranging from 81% to 92%, compared to that found in our study (52.9%). 10,11,18 In HIV-uninfected patients, our data was similar to other studies performed in Brazil, which describe the prevalence of C. albicans isolated in vaginal samples ranging from 60% to 80% 19,20 and in other countries where the prevalence of C. albicans in vaginal samples ranges between 80% to 90%. 1,11,21,22 A higher diversity of non-albicans species was found in HIV-infected patients compared to uninfected controls.…”
Section: Discussionsupporting
confidence: 89%
“…7,8 Factors which predispose to VVC include: pregnancy, uncontrolled diabetes mellitus, corticosteroids or systemic/ vaginal antibiotic therapy, HIV infection, and Candida vaginal colonization (CVC). 9,10 The frequency of VVC caused by other Candida species, such as Candida tropicalis, Candida glabrata, and Candida krusei is increasing, especially in HIV-infected women. 5,8,11 C. albicans and C. glabrata are responsible for the majority of VVC cases in HIV-infected women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozcan et al (2006) reported that C. glabrata is responsible for 14% of infections in immune competent women. Candida is a member of normal flora in vagina and oral cavity; however, there are many predisposing factors that can lead to these infections such as pregnancy, long term use of antibiotics, diabetes mellitus, using of corticosteroids, HIV infection, and being immunocompromised (Fidel and Sobel, 1996;Duerr et al, 1997Duerr et al, , 2003Corsello et al, 2003;Beltramene et al, 2006). *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%